1998
DOI: 10.1017/s1355617798466050
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological characteristics of five children with the Landau-Kleffner syndrome: Dissociation of auditory and phonological discrimination

Abstract: The Landau-Kleffner Syndrome (LKS) is characterized by acquired receptive aphasia and EEG abnormality with onset between the ages of 3 and 8 years. This study presents neuropsychological assessments in 5 children with LKS. The aims were (1) to specify the neuropsychological deficits characteristic of these children; and (2) to clarify the nature of the receptive aphasia by comparing nonverbal and verbal auditory discrimination. Receptive aphasia was present in all children. Retardation, poor motor coordination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 27 publications
0
14
0
2
Order By: Relevance
“…The timing of the regression and the features of the language impairment are important considerations to orientate the paediatrician to the possibility of autism as opposed to other conditions that are associated with loss of speech (table 5). 35 36 37 38 39 40 Electroencephalography (EEG) study is not indicated in autism unless it is part of the clinical work up for epilepsy.…”
Section: Regressionmentioning
confidence: 99%
“…The timing of the regression and the features of the language impairment are important considerations to orientate the paediatrician to the possibility of autism as opposed to other conditions that are associated with loss of speech (table 5). 35 36 37 38 39 40 Electroencephalography (EEG) study is not indicated in autism unless it is part of the clinical work up for epilepsy.…”
Section: Regressionmentioning
confidence: 99%
“…The major feature of the disease is the inability to understand spoken language; this has in turn been interpreted as reflecting an impairment of auditory phonological discrimination,26 a generalised auditory agnosia rather than a phonological decoding deficit,27 or a phonological deficit underlined by insensibility to loudness and a defect in temporal resolution 28. The length of electrical status epilepticus in sleep has a strong negative correlation with receptive as well as expressive language scores, highlighting the need for timely medical or surgical intervention 29…”
Section: Classificationmentioning
confidence: 99%
“…Although referred to as an epileptic aphasia (Caraballo et al, 2014;Korkman, Granstrom, Appelquist, & Liukkonen, 1998), it is estimated that only about 30% individuals with LKS experience generalized seizures (Stefanatos, 2011). In many cases, the continuous spikes and waves occur only during slow wave sleep (CSWS) or are associated with electrical status epilepticus in sleep (ESES; Nickels & Wirrell, 2008).…”
Section: Introductionmentioning
confidence: 99%